The Effect Of Work Discipline On Employee Performance Through Work Motivation In The Office Of The Agency Regional Disaster In Dairi Regency - Roy Endharto Tumanggor; Mesra B (Yayasan Multidimensi Kreatif, 2025)
A thorough understanding of the relationship between work discipline, motivation, and employee performance is essential to improve organizational effectiveness at the Dairi Regency Regional Disaster Management Agency (BPBD) Office. This understanding can optimize employee performance and support the achievement of organizational goals. The purpose of this study is to find out and analyze the influence of Work Discipline on Employee Performance that is intervened by Work Motivation at the Office of the Dairi Regency Regional Disaster Management Agency. This research was conducted with a causal associative quantitative approach. The sample used was all employees, with a total of 43 (forty-three) people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that 1) There is an influence of Work Discipline on Employee Performance. where the T-statistic value is 3.083 < 1.96 and the P-Value is 0.000< 0.05. 2) Work Discipline has a positive and significant effect on Work Motivation with a T-Statistical value of 22.008> 1.96 and a P-Value value of 0.000 < 0.05 which means that if Work Discipline is improved, the work motivation of employees will increase. 3) Work Discipline has a positive and significant effect on Work Motivation with a T-Statistical value of 22.008> 1.96 and a P-Value of 0.000 < 0.05 which means that if Work Discipline is improved, Employee Work Motivation will increase and 4) Work Motivation is able to intervene in the influence between Work Discipline and Employee Performance with the results of a T-Statistical value of 4.008 > 1.96 and a P-Value of 0.000 < 0.05. The implication of these findings is that management needs to consider the implementation of appropriate Work Motivation development strategies, along with Work Discipline practices, to create a Work environment that supports and encourages productive and innovative Employee Performance.